The probability distribution of daily rainfall distribution in Klang Valley - Intan Najiha Akhmar, Saharuddin (2017)
Distribution of daily rainfall in Klang Valley in Selangor was selected because many flash flood events were occurred. The existing system of drainage and infrastructures were designed based on historical rainfall data, but the capacity of the drainage network will not be sufficient enough with high intensive short duration rainfall which is expected to change due to global climate alteration. The main objective of this study was to assess the probability distribution of daily rainfall distribution in Klang Valley, Malaysia. The study has been specified into five districts in Klang valley which is Petaling Jaya, Wilayah Persekutuan, Gombak, Klang and Hulu Langat. The annual maximum series data were collected from year 1995 until 2015 from 17 stations. In this study, Normal and Log-Pearson Type III are identified to evaluate the best fit probability. Based on the analysis of goodness of fit tests, Log-Pearson Type III distributions prove to be the most appropriate distribution for annual maximum daily rainfall at all stations under study for Klang Valley river basin for both Chi-Square and Anderson-Darling test.